PEMBERDAYAAN MASYARAKAT MELALUI BADAN USAHA MILIK DESA “NGINGAS MAKMUR ABADI” DESA NGINGAS KECAMATAN WARU KABUPATEN SIDOARJO - Bariq Rakhmadian; Lukman Arif (Journal Publicuho, 2023)
Village community empowerment is carried out to develop independence and improve community welfare by increasing skills and abilities in managing and utilizing existing resources. This study aims to analyze and describe the process of Community Empowerment through Village-Owned Enterprises "Ngingas Makmur Abadi" Ngingas Village, Waru District, Sidoarjo Regency. In this study, the indicators used are studied from 3 (three) aspects: enabling, empowering and protecting. This type of research uses descriptive qualitative research, with data collection techniques of interviews, observation, and documentation. The results of the study explain that the community empowerment process carried out by the Village-Owned Enterprise "Ngingas Makmur Abadi" has been carried out quite well, it can be seen that two aspects of the indicators, namely Enabling and Empowering, have been implemented well, but one aspect of the Protecting indicator still has some constraints. even so, BUMDes Ngigas Makmur Abadi Community Empowerment has contributed to increasing PADes (Village Original Income) and Strengthening the Economy.